Currency Speculation in Fixed Exchange Rate Regimes Theory and Empirical Evidence - Zenker, Anja.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
Speculative currency crises seem to have become a common and inevitable phenomenon in the international monetary system. Against this background, various approaches have been developed by economists to cover the broad range of situations in which balance-of-payments crises occurred. Anja Zenker provides a comprehensive insight into the body of theoretical and empirical literature about currency speculation in fixed exchange rate regimes. The author discusses different generations of theoretical models and their empirical relevance in recent currency crises. Moreover, she considers diverse policy options which attempt to avoid speculative attacks on exchange rate pegs. Contents Classification and Features of Fixed Exchange Rate Regimes Theories of Currency Speculation in Fixed Exchange Rate Regimes Empirical Evidence on Currency Crisis in Fixed Exchange Rate Regimes Policy Options Targets Teachers and students of Economic Sciences with focus on Monetary Economics, International Macroeconomics, International Finance Executives and Specialists in the field of monetary policies The Author Anja Zenker is a lecturer and PhD student at the Department of Economics and Business Administration (Chair in Public Finance) of the Chemnitz University of Technology. She holds a MSc in Economics and a Bachelor in European Studies with Economical Science.
Keywords: Economics; Economic policy; Finance; Economics/Management Science; Financial Economics; Economic Policy; Business/Management Science, general